“FEATURES OF THE USE OF ANGLICISMS IN RUSSIAN-LANGUAGE ADVERTISING” - Bazarbaeva , Bibinaz Kenesbay qizi (Educational Research in Universal Sciences, 2023)
This dissertation is devoted to English borrowings in Russian advertising. The topic of Anglicisms in the Russian language is quite popular and is the object of research for many both domestic and foreign linguists. Interest in this problem has not waned over time, which indicates its multifaceted nature and inexhaustibility. Russian advertising, the language of which is closely related to linguistic changes and reflects the main trends in language development, has absorbed a large number of Anglicisms.